2016
DOI: 10.1111/jdi.12519
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin‐19 and angiopoietin‐2 with vascular complications in type 2 diabetes

Abstract: Aims/IntroductionThe aim of the present study was to investigate the role of interleukin‐19 (IL‐19) in angiogenesis of type 2 diabetes mellitus with complications, and to assess the relationship of serum IL‐19 and angiopoietin‐2 (Ang‐2) in type 2 diabetes mellitus.Materials and MethodsThe group studied comprised of 240 patients with type 2 diabetes mellitus (132 men and 108 women), and included macrovascular complications, microvascular complications and type 2 diabetes mellitus without vascular complications.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“… 10 , 11 IL-19 can be detected in human monocytes, 12 and the expression of IL-19 can be enhanced by stimulating B and T lymphocytes. 13 Studies show that increased IL-19 is involved in the incidence of autoimmune diseases 12 such as psoriasis, asthma, and rheumatoid arthritis by upregulating pro-inflammatory cytokines. 14 Monocytes treated by IL-19 induce the production of IL-6, tumor necrosis factor-α (TNF-α), and reactive oxygen metabolites, which play a pro-inflammatory role in the development of COPD.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 IL-19 can be detected in human monocytes, 12 and the expression of IL-19 can be enhanced by stimulating B and T lymphocytes. 13 Studies show that increased IL-19 is involved in the incidence of autoimmune diseases 12 such as psoriasis, asthma, and rheumatoid arthritis by upregulating pro-inflammatory cytokines. 14 Monocytes treated by IL-19 induce the production of IL-6, tumor necrosis factor-α (TNF-α), and reactive oxygen metabolites, which play a pro-inflammatory role in the development of COPD.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have revealed that the roles of IL-19 in development of vascular inflammatory diseases such as atherosclerosis, restenosis, and coronary artery transplant vasculopathy. Our previous also reported that IL-19 is closely related to T2DM with vascular complications [ 21 ]. However, whether there are some association between IL-19 concentration and DN have not been revealed clearly yet.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that serum Ang2 levels in T2DM patients with angiopathy were significantly higher than in patients without angiopathy and were correlated with HOMA-IR and HbA1c [69]. A positive correlation was also recently found between levels of Ang2 and IL-19, a cytokine associated with a number of concurrent microvascular and macrovascular lesions [70,71]. In diabetic nephropathy, Ang2 is also correlated with IL-18, and in high glucose conditions, Ang2 induced IL-18 expression.…”
Section: Ang1 and Ang2 In Diabetic Vascular Complicationsmentioning
confidence: 89%